1980
DOI: 10.2136/sssaj1980.03615995004400020048x
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Flooding Effects on Alfalfa Mortality, Soil Oxygen Concentrations, and Matric Potential in a Silty Clay Loam Soil

Abstract: Soil oxygen levels and soil water matric potentials were measured at the 15‐, 30‐, and 60‐cm depths in plots subjected to flooding times of 15, 25, 35, and 45 hours. A decrease to 6% O2 or less in the soil for > 24 hours resulted in substantial losses of alfalfa (Medicago sativa L.). Soil O2 content decreased more at the 15‐cm depth as compared with the 30‐ or 60‐cm depths because of higher matric potential. The critical matric potential that restricted O2 movement was about −11 cbars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The 0 2 and Eh values ranged between 20 % and about 480 mV, close to the soil surface, and around 7 % and -100 mV in the vicinity of the water table, respectively. This low value of 0 2 is comperable to the findings of Meek et al (1980) who found the oxygen to decrease to 6 % or less under a similar condition. The 0 2 and Eh changes with wather table depth, or Z, are mathematically expressed by quadratic polonominal equations with determination coefficients (r2) being 0.99 and 0.96 for 0 2 and Eh, respectively, which reflect a strong dependancy of both 0 2 and Eh on the water table depth, or Z.…”
Section: Resultssupporting
confidence: 68%
“…The 0 2 and Eh values ranged between 20 % and about 480 mV, close to the soil surface, and around 7 % and -100 mV in the vicinity of the water table, respectively. This low value of 0 2 is comperable to the findings of Meek et al (1980) who found the oxygen to decrease to 6 % or less under a similar condition. The 0 2 and Eh changes with wather table depth, or Z, are mathematically expressed by quadratic polonominal equations with determination coefficients (r2) being 0.99 and 0.96 for 0 2 and Eh, respectively, which reflect a strong dependancy of both 0 2 and Eh on the water table depth, or Z.…”
Section: Resultssupporting
confidence: 68%